(untitled) (Cardiovascular Journal, 2013)
Background: Nearly 40% of patients presenting with Non ST-Segment Elevation Myocardial Infarction (NSTEMI) have Chronic Kidney Disease (CKD). CKD is a powerful predictor of adverse events among NSTEMI patients. The purpose of the present study was to evaluate the in-hospital outcome of patients with Chronic Kidney Disease presenting with Non ST-Segment Elevation Myocardial Infarction. Methods: In this prospective observational study a total of 128 patients with NSTEMI were enrolled. They were divided equally in group I (NSTEMI with CKD) and group II (NSTEMI with normal renal function) on the basis of estimated glomerular filtration rate. Patients were considered to have CKD if he/she had documented history of CKD or estimated glomerular filtration rate <60 mL/min/1.73 m². Presence of inhospital complications was identified. Results: Patients with CKD were significantly older, with a greater prevalence of hypertension, diabetes mellitus, lower left ventricular ejection fraction, and lower haemoglobin level compared with those without CKD. CKD patients had more atypical presentation during admission. In-hospital complications were significantly higher in CKD patients presenting with NSTEMI. Conclusion: CKD strongly predicts adverse in-hospital outcome among NSTEMI patients. DOI: http://dx.doi.org/10.3329/cardio.v5i2.14305 Cardiovasc. j. 2013; 5(2): 146-153